Instagram Sebagai Ruang Cyberbullying untuk Memenuhi Kebutuhan Gaya Hidup Hedonis Siswa Sekolah Menengah Atas - Zamzamima, Elcindi Lazuardin; Hambali, IM; Apriani, Rizka (citeus, 2025)
Recently, social media has been an integral part of adolescents’ life, serving as a medium for their self-actualization. On the other hand, adolescents use social media for hostile activities, such as bullying. This study describes Instagram as a platform for cyberbullying as it allows students to demonstrate their hedonist lifestyle. In this study, we used a descriptive qualitative approach. For the data collection, we involved two senior high school students, who were selected through purposive sampling with the criteria of undertaking cyberbullying acts to fulfill their needs for a hedonist lifestyle. The data were collected through structured interviews and documentation. The obtained data were analyzed using the Miles and Huberman model, which consisted of three stages, namely data reduction, data presentation, and conclusion making. The data validity was examined using the data triangulation technique. Our findings suggested that students commit cyberbullying to fulfill their lifestyle and attain recognition from their surroundings. Thus, the school’s guidance and counseling service should further regard our findings in providing the guidance and counseling services.